Health-related quality of life after kidney transplantation in comparison intermittent hemodialysis, peritoneal dialysis, and normal controls - (:unkn) unknown (ELSEVIER SCIENCE INC, 2006)
The purpose of this study was to compare the quality of life (QOL) in renal transplantation patients. QOL is one of the important indicators of the effects of medical treatment. In this cross-sectional study, QOL was analyzed in 302 renal transplant recipients compared with 64 hemodialysis (HD) patients, 207 (PD) peritoneal dialysis patients, and 278 normal controls (NC) matched as closely as possible to the grafted patients regarding age, gender, education, and occupation. All groups were asked to estimate their subjective QOL by responding to sociodemographic data, Turkish adapted instruments of the Nottingham Health profile (NHP), and the Short-form 36 (SF-36). Transplant recipients were significantly younger than the HD and PD patients (P < .0001.). There was no statistically significant differences between normal controls and transplant patients ages. Among the three renal replacement methods, QOL in transplants was clearly better than that in HD or PD patients (P < .0001). The QOL measured by the NHP and SF-36 scale showed that the normal population was statistically significantly better than the transplant recipients (P < .0001). Transplant renal replacement therapy provides a better QOL compared with other replacement methods.
Keywords: HRQOL; VARIABLES; VERSION